2014
DOI: 10.1007/s40266-014-0170-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis C in the Aged: Much Ado About Nothing or Nothing to Do?

Abstract: Hepatitis C is a common infection worldwide. It is a major cause of cirrhosis and its complications, including hepatocellular carcinoma and liver transplantation. Treatment of hepatitis C has dramatically improved since its discovery. Current treatment includes pegylated interferon and ribavirin, and the addition of the protease inhibitors telaprevir, boceprevir, or simeprevir, or the polymerase inhibitor sofosbuvir. The rate of sustained viral response, considered a cure, now approaches 80 %. These treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…97 Malnick et al (2014) reviewed several clinical trials of various HCV treatments and found that those aged 65 years or older were often excluded from trials, but where data were available, older patients discontinued treatment at a higher rate and/or achieved SVR at a lower rate than younger study participants. 98 Narciso-Schiavon et al (2010) reported that although women had more adverse events than men, SVR rates were similar between the sexes. 99 In those receiving liver transplants and experiencing HCV recurrence, SVR rates in genotype 1 patients were lower in women than men.…”
Section: Demographic Predictors In Hepatitis C Curementioning
confidence: 99%
“…97 Malnick et al (2014) reviewed several clinical trials of various HCV treatments and found that those aged 65 years or older were often excluded from trials, but where data were available, older patients discontinued treatment at a higher rate and/or achieved SVR at a lower rate than younger study participants. 98 Narciso-Schiavon et al (2010) reported that although women had more adverse events than men, SVR rates were similar between the sexes. 99 In those receiving liver transplants and experiencing HCV recurrence, SVR rates in genotype 1 patients were lower in women than men.…”
Section: Demographic Predictors In Hepatitis C Curementioning
confidence: 99%
“…While hepatitis C is more prevalent in the elderly population, the efficacy and safety of treating aged patients with antivirals is a source of debate, since this subgroup of patients seems to be more sensitive to develop side effects. 138 In the field of liver transplantation, a study showed that recipients aged more than 60 years exhibit lower survival rates compared with those aged between 45 and 60 years. 139 In addition, in a recent report aimed at testing safety of statins in patients with advanced cirrhosis, the group of patients exhibiting signs of toxicity was, intriguingly, older than the one with no evidence of toxic effects.…”
Section: Toward a Personalized Medicine Considering Patient's Agementioning
confidence: 99%
“…For chronic hepatitis C, the risk for fibrosis increases with the duration of the infection and age greater than 50 years [17 -19]. Treatment with peg-interferon alfa based treatment regimens is often associated with lower sustained virological response rates and poorer tolerability in older compared to young individuals [20], however, these limitations can be overcome by interferon-free combination therapies of direct antiviral agents [6 -9]. We therefore determined the frequency of HBV and HCV infection by prospectively screening patients in a German tertiary referral centre for the presence of HBsAg and anti-HCV.…”
mentioning
confidence: 99%
“…Interferon-free treatment options of chronic hepatitis B and C have continuously developed through the last years and offer high antiviral efficacy in combination with good clinical toler- ability. These properties of HBV nucleos(t)ide analogues and direct antiviral agents against HCV allow an extension of treatment indications to populations precluded from interferon-based therapeutic options so far [20]. Therefore, identification of HBsAg and anti-HCV positive individuals by systematic screening of elderly hospitalized patientsa population which has not been adequately addressed by the recent German national health care survey and two large studies in emergency departments and the primary care physician's settings [14,25,26]adds important information to the efforts to increase the number of newly diag- nosed hepatitis patients and potentially extend treatment uptake in order to reduce the number of virus-induced end-stage liver diseases in the future [12].…”
mentioning
confidence: 99%